SMART CITIES: THE COMBINATIONOF TECHNOLOGY AND ARCHITECTURE (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
the 21st century is a century of urbanization and technological progress that seeks to make cities more accessible, safe and environmentally sustainable. The Smart city concept is aimed at optimizing urban management using information technology, efficient use of resources and improving the quality of life of the population. The concept is based on IoT (Internet of Things), artificial intelligence, large-scale data analysis, and automated systems